Market-Capital beneath the Skin of “Fear Factories”: The Autobiography of an English-Speaker-of-Other-Languages Educator - Saha, Shuvo (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2025)
Curricular theorist Kent Den Heyer’s (2018) framing of schools as “fear factories” prompted me to reflect on how the curriculum I encountered as a student may have instilled fear in me, and how this fear may have shaped my role as an ESOL educator from the Global South. This autobiographical study explores my experiences as both a learner and a post-secondary educator through a reflexive lens. Drawing on diary entries, I crafted an autobiographical narrative (Pavlenko, 2007). I also created a collage using personal and professional images surrounding a 3D model of my head (Davis & Butler-Kisber, 1999; Rijke, 2023). I analyzed these artifacts using critical theory lenses (Rist, 2014; Walker, 2012). Findings suggest that developmentalist and disability discourses have contributed to a market-capitalist curriculum that cultivated fear in my education, leaving a lingering apprehension that continues to shape my current identity as an educator.